Legal Protection for Victims in Fake Investment on Telegram - Zeno Eronu Zalukhu; Yasmirah Mandasari Saragih; Fauzan Fauzan (Green Social: International Journal of Law and Civil Affairs, 2025)
The Unitary State of the Republic of Indonesia is a country of law that guarantees justice and protection for its citizens. This protection is stated in the 1945 Constitution Article 28G paragraph (1), namely: "Everyone has the right to protection of themselves, their families, their honor, their dignity, and their property under their control, and has the right to a sense of security and protection from the threat of fear to do or not do something that is a basic human right". Fraudulent investment is an act of investment fraud, where the perpetrator asks for funds to be invested in a business that is in fact illegal and does not have a permit from the competent authority. This study aims to determine the form of legal protection for victims and to find out how to avoid fraudulent investment. The research method used is qualitative by using the type of literature study of journal analysis, or other media to become a literature reading that is arranged coherently and neatly. This literature study will look for various relevant articles by citing from various sources.